2023
DOI: 10.54371/jiip.v6i8.2672
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Pencarian Informasi Politik di Media Sosial Bagi Pemilih Pemula Kota Surabaya

Abstract: Perkembangan teknologi komunikasi dan informasi di Indonesia telah menghadirkan media baru yaitu media sosial. Beralihnya media konvensional menjadi media sosial menimbulkan perubahan pencarian informasi. Manusia akan melakukan berbagai cara untuk memenuhi kebutuhan informasinya yang akan menimbulkan perilaku pencarian informasi yang berbeda juga. Tujuan dari penelitian ini adalah mengetahui bagaimana perilaku pencarian informasi politik di media sosial bagi pemilih pemula di Kota Surabaya. Metode yang digunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…fashion [19] and religion [20]. As for the social media accessed by Generation Z, it is highly diverse, including websites, WhatsApp, Instagram, Facebook, TikTok, LINE, Google Meet, and Zoom Meeting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…fashion [19] and religion [20]. As for the social media accessed by Generation Z, it is highly diverse, including websites, WhatsApp, Instagram, Facebook, TikTok, LINE, Google Meet, and Zoom Meeting.…”
Section: Resultsmentioning
confidence: 99%
“…[24] The fashion industry is currently experiencing rapid growth; it is not surprising that Gen Z utilizes social media to seek information related to fashion. [19] The study found that information sought through the Instagram social media platform regarding fashion products includes specifications such as material, model, color, size, and price. This information serves as the primary consideration for Gen Z before deciding to purchase the product.…”
Section: Resultsmentioning
confidence: 99%